A very deep Chandra view of metals, sloshing and feedback in the Centaurus cluster of galaxies - Sanders, J; Fabian, A; Taylor, G; Russell, H; Blundell, K; Canning, R; Hlavacek-Larrondo, J; Walker, S; Grimes, C (Oxford University Press, 2016)
We examine deep Chandra X-ray observations of the Centaurus cluster of galaxies, Abell 3526. Applying a gradient magnitude filter reveals a wealth of structure, from filamentary soft emission on 100pc (0.5 arcsec) scales close to the nucleus to features 10s of kpc in size at larger radii. The cluster contains multiple high-metallicity regions with sharp edges. Relative to an azimuthal average, the deviations of metallicity and surface brightness are correlated, and the temperature is inversely correlated, as expected if the larger scale asymmetries in the cluster are dominated by sloshing motions. Around the western cold front are a series of ~7 kpc 'notches', suggestive of Kelvin-Helmholtz instabilities. The cold front width varies from 4 kpc down to close to the electron mean free path. Inside the front are multiple metallicity blobs on scales of 5-10 kpc, which could have been uplifted by AGN activity, also explaining the central metallicity drop and flat inner metallicity profile. Close to the nucleus are multiple shocks, including a 1.9-kpc-radius inner shell-like structure and a weak 1.1-1.4 Mach number shock around the central cavities. Within a 10 kpc radius are 9 depressions in surface brightness, several of which appear to be associated with radio emission. The shocks and cavities imply that the nucleus has been repeatedly active on 5-10 Myr timescales, indicating a tight balance between heating and cooling. We confirm the presence of a series of linear quasi-periodic structures. If they are sound waves, the ~5 kpc spacing implies a period of 6 Myr, similar to the ages of the shocks and cavities. Alternatively, these structures may be Kelvin-Helmholtz instabilities, their associated turbulence or amplified magnetic field layers.